EVALUASI PENERAPAN INVENTORY SYSTEM MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Christian, Ade (Jurnal Pilar Nusa Mandiri, 2019)
This research aim was to evaluate and analyze Inventory System implementation using the Technology Acceptance Model (TAM). The data used in this research are primary data and secondary data, collected using several data collection techniques, such as observation, interviews, questionnaires, and literature review. The variables in this research are Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Perceived Enjoyment, Acceptance of IT. Processing and analysis of data in this research were using descriptive statistical analysis and simple linear regression analysis, which done by the support of the Application SPSS version 21. The results of this research are as follows 1) perceived ease of use Inventory System has given a positive and significant influence on Perceived Usefulness. 2) Perceived Usefulness Inventory System has given a positive and significant influence on user’s attitude. 3) Perceived Ease of Use has given positive and significant influence on the user’s attitude. 4) Perceived Enjoyment has given positive and significant influence on the user’s attitude. 5) Perceived Usefulness has given a positive and significant influence on the acceptance of IT. 6) Perceived Ease of Use has given positive and significant influence on the acceptance of IT.